Politics, Property and Law in the Philippine Uplands - Wiber, Melanie G. (Book collections on Project MUSE., 2006)
The Ibaloi village of Kabayan Poblacion combines a subsistence agricultural economy with a market economy that has grown up as a result of subsequent waves of colonization. The Spanish arrived in the sixteenth century, following the trail of gold and slave-bearing Chinese trade junks, and were followed in 1898 by the Americans. The Ibaloi, who were gold miners and traders, cattle barons and vegetable producers, have since then come to be known as an Hispanicized uplands people, acculturated to Western ways and struggling to come to grips with new economic realities. This book examines the I.